Challenges facing green space: is statute the answer?. Issue 1 (4th March 2019) - Dickinson, Jill; Bennett, Ellen; Marson, James
Abstract : Purpose: Against a backdrop of austerity, characterised by public-sector funding cuts and a devolutionary agenda, this paper aims to explore how legislation might address two inter-related challenges which public urban green space ("greenspace) faces in England and Wales, namely, responsibility for provision and identification of supporting funds. It focuses on two proposals: first, the introduction of legislative powers to enable local authorities to create user-charging schemes, and second, the imposition of a local authority statutory duty to provide greenspace. Design/methodology/approach: Adopting a traditional doctrinal approach, this exploratory study provides a synthesis and analysis of statutory materials. Findings: While the study considers debates around user-charging schemes, it suggests that the imposition of a statutory duty to provide greenspace would provide a more equitable and effective solution. Research limitations/implications: This paper calls for further research to establish the detail of such a statutory duty and how it might operate in practice. Practical implications: There is an appetite amongst local authority stakeholders in England and Wales for such a statutory duty to better enable them to access the requisite underpinning funding. Social implications: Imposing a statutory duty would help in protecting the well-established social, economic and environmental benefits associated with greenspace. Originality/value: This multi-disciplinary research considers the inter-relationship between two key greenspace challenges: responsibility for provision and funding. It identifies and evaluates a potential model for imposing a greenspace statutory duty, which could address some of these issues.